Trend of Occupational Injuries/Diseases in Pakistan: Index Value Analysis of Injured Employed Persons from 2001–02 to 2012–13 - Abbas, Mohsin (Saf Health Work, 2015)
BACKGROUND: The present study aimed to analyze the index value trends of injured employed persons (IEPs) covered in Pakistan Labour Force Surveys from 2001–02 to 2012–13. METHODS: The index value method based on reference years and reference groups was used to analyze the IEP trends in terms of different criteria such as gender, area, employment status, industry types, occupational groups, types of injury, injured body parts, and treatment received. The Pearson correlation coefficient analysis was also performed to investigate the inter-relationship of different occupational variables. RESULTS: The values of IEP increased at the end of the studied year in industry divisions such as agriculture, forestry, hunting, and fishing, followed by in manufacturing and construction industry divisions. People associated with major occupations (such as skilled agricultural and fishery workers) and elementary (unskilled) occupations were found to be at an increasing risk of occupational injuries/diseases with an increasing IEP trend. Types of occupational injuries such as sprain or strain, superficial injury, and dislocation increased during the studied years. Major injured parts of body such as upper limb and lower limb found with increasing trend. Types of treatment received, including hospitalization and no treatment, were found to decrease. Increased IEP can be justified due to inadequate health care facilities, especially in rural areas by increased IEP in terms of gender, areas, received treatment, occupational groups and employment status as results found after Pearson correlation coefficient analysis. CONCLUSION: The increasing trend in the IEP% of the total employed persons due to agrarian activities shows that there is a need to improve health care setups in rural areas of Pakistan.